A densification equation derived from the stress-deformation analysis of uniaxial cold compaction of metal powder mixes. (27th May 2018) - Molinari, Alberto; Cristofolini, Ilaria; Pederzini, Gianluca; Rambelli, Alex
ABSTRACT: A new densification equation for uniaxial cold compaction of four low alloy steel powders was determined from the deformation vs. mean axial stress correlation. Both deformation and stress are averaged along the height of the powder column. A power law relation, with two parameters representing the plasticity and the inverse of the resistance to deformation (densification) of the powder mix, respectively, fits the curves that are divided in two steps, distinguished by the prevailingdeformation/densification mechanism (rearrangement or plastic deformation). Densification of the four powder mixes is greatly affected by the starting density in the die cavity, while the chemical composition of the base iron powder has a less significant effect.